One new spesies and one new record of the genus zaglyptus foester (hymenoptera: ichneumonidae: pimplinae) from Malaysia - Alia Rizki,; Idris , A.B (Pusat Sistematik Serangga ,UKM, 2010)
One new species, zaglyptus sp.nove and new record, zaglyptus nigrolineatus gupta from Malaysia are described. One holotype species, zaglyptus indicus nigrithorax gupta is also redescribed. A key to species is provided.